Core level shifts of intercalated graphene. (4th November 2016) - Schröder, Ulrike A; Petrović, Marin; Gerber, Timm; Martínez-Galera, Antonio J; Grånäs, Elin; Arman, Mohammad A; Herbig, Charlotte; Schnadt, Joachim; Kralj, Marko; Knudsen, Jan; Michely, Thomas
Abstract: Through intercalation of metals and gases the Dirac cone of graphene on Ir(111) can be shifted with respect to the Fermi level without becoming destroyed by strong hybridization. Here, we use x-ray photoelectron spectroscopy to measure the C 1s core level shift (CLS) of graphene in contact with a number of structurally well-defined intercalation layers (O, H, Eu, and Cs). By analysis of our own and additional literature data for decoupled graphene, the C 1s CLS is found to be a non-monotonic function of the doping level. For small doping levels the shifts are well described by a rigid band model. However, at larger doping levels, a second effect comes into play which is proportional to the transferred charge and counteracts the rigid band shift. Moreover, not only the position, but also the C 1s peak shape displays a unique evolution as a function of doping level. Our conclusions are supported by intercalation experiments with Li, with which, due to the absence of phase separation, the doping level of graphene can be continuously tuned.